Retroperitoneal fibrosis due to malignancy: A case report - (:unkn) unknown (Kluwer Academic Publishers, 1995)
Retroperitoneal fibrosis is idiopathic in two thirds of cases and is found most commonly as an isolated fibrotic plaque centered over the lumbar spine and entrapping one or both ureters. It has been postulated that fibrosis in the idiopathic cases results from a hypersensitivity reaction to antigens leaking into the retroperitoneum from atheromatous plaques in the aorta or common iliac arteries. In the remaining one third of cases, causes include ergot-derivative drugs, retroperitoneal haemorrhage or urine extravasation, and a desmoplastic response to a variety of tumours. © 1995 Akadémiai Kiadó.